This system of equations has no solution, the 2 lines will never cross
A fisherman can row upstream at 4 mph and downstream at 6 mph. He started rowing upstream until he got tired and then rowed downstream to his starting point. The distance of how far the fisherman row if the entire trip took 2 hours is 9.6 miles
<u />
The speed of an object refers to the change of the object's distance within a specified time.
Mathematically, we can have;
![\mathbf{Speed =\dfrac{distance}{time}}](https://tex.z-dn.net/?f=%5Cmathbf%7BSpeed%20%3D%5Cdfrac%7Bdistance%7D%7Btime%7D%7D)
Distance = speed × time
From the information given;
- The fisherman row upstream for 4 miles/ hour.
- The distance covered by the fisherman = 4 × t₁ ----- (1)
- The fisherman row downstream at 6 miles/ hour
- The distance covered by the fisherman = 6 × t₂ ------ (2)
- SInce it took the entire trip 2 hours, we can infer that:
From equation (2), replace the above value of t₂ into equation (2)
- d = 6 t₂
- d = 6(2 - t₁)
- d = 12 - 6t₁
From equation (1)
Equation both distance together, we have:
- 12 - 6t₁ = 4t₁
- 12 = 4t₁ + 6t₁
- 12 = 10t₁
- t₁ = 12/10
- t₁ = 1.2 hours
From t₂ = 2 - t₁
- t₂ = 2 - 1.2
- t₂ = 0.8 hours
From d = 4t₁
Replace t₁ with 1.2 hours
- d = 4(1.2 hours)
- d = 4.8 miles
Also, from d = 6t₂
Therefore, we can conclude that the distance of how far the fisherman row if the entire trip took 2 hours is (4.8+4.8) miles = 9.6 miles
Learn more about distance here:
brainly.com/question/12319416?referrer=searchResults
A compound inequality is used to combined multiple inequalities.
- <em>The compound inequality is: </em>
<em>.</em> - <em>The solution to the compound inequality is: </em>
<em />
We have:
![12 \le A \le 36](https://tex.z-dn.net/?f=12%20%5Cle%20A%20%5Cle%2036)
![Length = 2x](https://tex.z-dn.net/?f=Length%20%3D%202x)
![Width = 3](https://tex.z-dn.net/?f=Width%20%3D%203)
The area of the rectangle is:
![A = Length \times Width](https://tex.z-dn.net/?f=A%20%3D%20Length%20%5Ctimes%20Width)
So, we have:
![A =2x \times 3](https://tex.z-dn.net/?f=A%20%3D2x%20%5Ctimes%203)
![A = 6x](https://tex.z-dn.net/?f=A%20%3D%206x)
Substitute 6x for A in ![12 \le A \le 36](https://tex.z-dn.net/?f=12%20%5Cle%20A%20%5Cle%2036)
![12 \le 6x \le 36](https://tex.z-dn.net/?f=12%20%5Cle%206x%20%5Cle%2036)
Divide through by 6
![2 \le x \le 6](https://tex.z-dn.net/?f=2%20%5Cle%20x%20%5Cle%206)
Hence,
- The compound inequality is:
. - The solution to the compound inequality is:
![2 \le x \le 6](https://tex.z-dn.net/?f=2%20%5Cle%20x%20%5Cle%206)
Read more about compound inequalities at:
brainly.com/question/17957246
Answer:
EIther 45 or 15
Step-by-step explanation:
Answer:
1125 cent or 11.25
Step-by-step explanation:
19*5=95 43*10=430